Synthesis and Self-Assembly Behavior of Double Ullazine-Based Polycyclic Aromatic Hydrocarbons - Richter, Marcus; Borkowski, Michal; Fu, Yubin; Dmitrieva, Evgenia; Popov, Alexey; Ma, Ji; Marszalek, Tomasz; Pisula, Wojciech; Feng, Xinliang (Organic Materials, 2021)
Polycyclic aromatic azomethine ylides (PAMY, 1) are versatile building blocks for the bottom-up synthesis of nitrogen-containing polycyclic aromatic hydrocarbons (N-PAHs). Although the chemistry of PAMY was already established few years ago, the cycloaddition of a double PAMY building block has not been reported so far. In this work, we demonstrate the first cycloaddition of a PAMY-dimer (6), which opens the access to three different alkyl ester-substituted N-PAHs with a laterally extended double ullazine scaffold (DU-1, DU-2 and DU-3). Interestingly, the cyclic voltammetry of DU-1–3 exhibited three reversible oxidation waves, which confirmed the electron-rich nature of the double ullazine scaffold. Furthermore, in situ spectroelectrochemistry study of ethylhexyl ester-substituted DU-3 revealed the formation of different cationic species with new absorption bands up to 1689 nm. Additionally, the influence of the attached substituents on the film formation and supramolecular organization in the thin films was investigated by polarized optical microscopy and grazing incidence wide-angle X-ray scattering.
Keywords: polycyclic aromatic hydrocarbons; nanographenes; polycyclic aromatic azomethine ylides; cycloaddition; ullazine